Electrical stimuli to increase cell proliferation on carbon nanotubes/mesoporous silica composites for drug delivery1. Issue 1 (30th July 2012) - Vila, M.; Cicuéndez, M.; Sánchez‐Marcos, J.; Fal‐Miyar, V.; Manzano, M.; Prieto, C.; Vallet‐Regi, M.
Abstract: The development of smart materials as bone implants is nowadays a challenging task to optimize their fast osteointegration. Nevertheless, no attempts have been done in joining the possibility of using electrical stimulation and drug delivery together in a material intended for bone tissue engineering. Moreover, the use of this synergy to induce bone healing is still limited until novel drug reservoirs material formulations allow an efficient applicability of the electrical stimuli. Herein, we present the biological response of osteoblasts cells, cultured over carbon nanotubes–mesoporous silica composites while exposed to external electrical stimulus. Moreover, its ability to function as drug delivery systems is also demonstrated. Bone cell metabolism was stimulated and mitochondrial activity was increased up to seven times in the presence of these composites under electrical stimulus, suggesting their potential application in bone regeneration processes. © 2012 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 101A:213–221, 2013.